Implicit Elements in the Argument Structure: The Problems of Interpretation and Methods of Reconstruction - Савчук, Татьяна (Respectus Philologicus, 2018)
The article presents the author’s model of research of the enthymematic argumentation created on the basis of the analysis of the Russian language and the Belarusian language articles on the humanities. The concept is based on a convergent approach. Its effectiveness is provided by the ability to integrate critical and descriptive dimensions of reasoning through the joint application of cognitive and pragmatic methodology. Normative criteria are provided by cognitive (logical) analysis: it assumes the use of deductive inference, which makes it possible to verify the formal correctness and meaningful validity of the unexpressed premises. The description of the mechanisms of understanding the implicit knowledge and evaluating its relevance is made by carrying out pragmatic analysis: it is associated with the probabilistic inference, which allows us to derive communicative implicatures. In the creation and interpretation of implicatures errors are possible. They manifest themselves in quantitative and qualitative distortion ofimplicit information. Prevention of errors depends on the high level of argumentative competence of the proponent and the recipient. The regularities of using the implicative-inferential justification mechanism are identical in the Russian and Belarusian discourses of the humanities.
Keywords: Argumentation; Implicit Structure; Interpretation; Reconstruction; Inference